Evaluation of Turkish illustrated story books on oral hygiene - Serpil Sağdıç; Zeynep Öztürk (BMC Oral Health)
Abstract Background The acquisition of oral hygiene habits during early childhood plays an important role in the prevention of dental caries. Illustrated storybooks can be an effective tool for teaching children oral hygiene behaviors. This study examined the content of available Turkish illustrated storybooks related to oral hygiene from various perspectives. Methods Internet searches were conducted for books related to oral hygiene. The publication year, price, page count, original language, image–text coherence, target audience age, reading level, author’s profession, and reference information of the books that met the inclusion criteria were recorded. The content of the books was evaluated based on the guidelines of the American Academy of Pediatric Dentistry (AAPD). Results A total of 33 books with relevant content fulfilled the inclusion criteria. The publication years of the books ranged from 2015 to 2023. The average price was 53.95 ± 27.71 liras, and the average number of pages was 28.06 ± 13.13. Thirteen of the books were originally written in Turkish, while the others were translated into Turkish. Most of the books were found to be very readable. Only three books were written by a dentist. Tooth brushing was the most frequently mentioned oral hygiene practice. Conclusions The books did not fully cover the AAPD guidelines. It is important for authors to consult professional sources or expert opinions to ensure the accuracy and comprehensiveness of the health information conveyed in their books.